Aspects of the biology of Boophilus decoloratus (Koch, 1844) (Acarina : ixodidae) - Londt, Jason G H (Jason Gilbert Hayden), 1943- (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1973)
1. The external morphology of all stages in the life cycle of B. decoloratus is described with the aid of scanning electron micrographs. 2. The biological activities of B. decoloratus during its parasitic cycle are examined with special reference to the course of feeding of all stages, and to the influence of the pharate nymph and adult conditions in accelerating the completion of the cycle. 3. The pattern of dropping of replete females is considered in relation to their weight and their time of drop-off. 4. The adult male population structure is described. Two distinct weight groups are reported and the taxonomic significance of these is discussed. 5. The preoviposition period duration of B .decoloratus was studied under laboratory conditions and found to be temperature dependent and humidity independent. Female size, as implied by their engorged weights, influenced the duration of the oviposition period: ticks weighing less than 20 mg possessed longer preoviposition periods. 6. The preoviposition period of B.decoloratus females under fluctuating macroclimatic conditions was studied and found to be long in duration. The implications of this are discussed in relation to laboratory findings and the summer build-up of this species in nature. 7. The duration of the oviposition period of B. decoloratus and the number of eggs produced during this period were studied under laboratory and field conditions. Both these parameters were found to be temperature dependent and uninfluenced by humidity. The significance of a temperature dependent oviposition period is discussed. 8. The minimum amount of 'blood' required by female ticks for oviposition of eggs was found to be approximately 16 mg. under laboratory conditions. 9. The oviposition behaviour of B. decoloratus females has been described and the water relations of ovipositing and non-ovipositing females were examined and discussed . 10. The effects of handling female ticks during their oviposition period was studied and females which were handled were found to produce significantly fewer eggs. The significance of this is discussed. 11. During preliminary experiments on the incubation period of B. decoloratus it was found that the viability of eggs laid during the first half of the oviposlting period was greater than for eggs laid in the second half of the period. The critical temperature of the 'wax' coating of eggs was found to be 42â °C while the critical humidity was approximately 70% R.H. (7,53 mmHg) at 26â °C. The implications of these findings are discussed. 12. The development of eggs, traced throughout the incubation period by monitoring the build-up of guanine spectrophotometrically, was studied under different humidity conditions . Successful development was found to be dependent on the water content of the eggs at the time of laying. As eggs were also found to be unable to take up water vapour from the atmosphere this finding is important evidence to support the suggestion that the survival of the egg stage largely determines the spacial distribution of larvae in the field. 13. Results of work done at constant, alternating and naturally fluctuating temperatures and humidities demonstrated that the duration of the incubation period of B.decoloratus is temperature dependent and humidity independent. The significance of this is discussed in relation to the findings of previous workers and to the biology of the species. 14. Egg viability (percentage hatch) was found to be humidity dependent and temperature independent. The implications of these findings are discussed. 15. Some of the problems associated with the assessment of the effects of climatic conditions on ticks are discussed. Special reference has been made to the advocation of using saturation deficit instead of relative humidity as the parameter indicative of environmental humidity in any biological study involving fluctuating humidity conditions. 16. The problems associated with having three variables (e.g. temperature, saturation deficit and incubation period duration) are discussed and reasons given for why contour diagrams have been used in this investigation. 17. A model of the interactions between the main abiotic factors of the environment (temperature and humidity) and the biological parameters studied during the second part of this investigation is presented. 18. The effects of climatic conditions on the life cycle and distribution of B.decoloratus are discussed. Special reference has been made to the available evidence explaining the summer build-up in tick numbers known to occur in nature and the way in which the present findings have helped in an understanding of the spacial distribution of B.decoloratus in the field.
Keywords: Ixodidae -- Development; Ticks -- Development; Boophilus -- Development